Exploring the relationships between Corporate Social Performance (CSP) and institutional shareholding for JSE-listed companies - Maliwa, Bonga (Department of Finance and Tax, 2018)
Globally institutional investors are taking an increased interest in companies' environmental, social and governance (ESG) disclosure and their corporate social responsibility (CSR) performance. Although the relationship between a company's Corporate Social Performance (CSP) and its institutional shareholding has been studied in a number of developed economies, this study fills a gap in the literature by investigating this link for JSE listed companies. Using Bloomberg's ESG and individual environmental, social, and governance disclosure scores as proxies for CSP, panel data regression methodologies are applied to a sample of 98 companies (254 company years) listed on the Johannesburg Stock Exchange from 2013 to 2016 to investigate the link between the different forms of CSP and institutional shareholding in South Africa. The study fails to establish a relationship between institutional shareholding and environmental and social based CSP, but finds a statistically significant positive relationship for governance based CSP. The results imply that, of the three CSP components, South African institutional shareholders in the studied sample mainly consider the governance component in their investment decisions, possibly because good corporate governance is associated with improved financial performance and the adoption of sustainability policies by the company.